Copper‐Catalyzed Aerobic Oxidative Cleavage of Unstrained Carbon‐Carbon Bonds of 1, 1‐Disubstituted Alkenes with Sulfonyl Hydrazides. Issue 4 (25th February 2021) - Yi, Dong; He, Linying; Qi, Zhongyu; Zhang, Zhijie; Li, Mengshun; Lu, Ji; Wei, Jun; Du, Xi; Fu, Qiang; Wei, Siping
Main observation and conclusion: Alkoxy radical‐mediated carbon‐carbon bond cleavages have emerged as a powerful strategy to complement traditional ionic‐type transformations. However, carbon‐carbon cleavage reaction triggered by alkoxy radical intermediate derived from the combination of alkyl radical and dioxygen, is scarce and underdeveloped. Herein, we report alkoxy radical, which was generated from alkyl radical and dioxygen, mediated selective cleavage of unstrained carbon‐carbon bond for the oxysulfonylation of 1, 1‐disubstituted alkenes, providing facile access to a variety of valuable β‐keto sulfones. Mechanistic experiments indicated alkoxy radical intermediate that underwent subsequent regioselective β‐scission might be involved in the reaction and preliminary computational studies were conducted to provide a detailed explanation on the regioselectivity of the C—C bond cleavage. Notably, the strategy was successfully applied for constructing uneasily obtained architecturally intriguing molecules. Abstract : Herein, we report alkoxy radical, which was generated from alkyl radical and dioxygen, mediated selective cleavage of unstrained carbon‐carbon bond for the oxysulfonylation of 1, 1‐disubstituted alkenes, providing facile access to a variety of valuable β‐keto sulfones. Importantly, the strategy was successfully applied for constructing uneasily obtained architecturally intriguing molecules.